Early amplitude-integrated electroencephalography for monitoring neonates at high risk for brain injury - Gabriel Fernando Todeschi Variane; Maurício Magalhães; Renato Gasperine; Heitor Castelo Branco Rodrigues Alves; Thiago Luiz Pereira Donoso Scoppetta; Rodrigo de Jesus Gonçalves Figueredo; Francisco Paulo Martins Rodrigues; Alexandre Netto; Marcelo Jenne Mimica; Clery Bernardi Gallacci
Abstract Objective: This study aimed to correlate amplitude-integrated electroencephalography findings with early outcomes, measured by mortality and neuroimaging findings, in a prospective cohort of infants at high risk for brain injury in this center in Brazil. Methods: This blinded prospective cohort study evaluated 23 preterm infants below 31 weeks of gestational age and 17 infants diagnosed with hypoxic-ischemic encephalopathy secondary to perinatal asphyxia, with gestational age greater than 36 weeks, monitored with amplitude-integrated electroencephalography in a public tertiary center from February 2014 to January 2015. Background activity (classified as continuous, discontinuous high-voltage, discontinuous low-voltage, burst-suppression, continuous low-voltage, or flat trace), presence of sleep-wake cycling, and presence of seizures were evaluated. Cranial ultrasonography in preterm infants and cranial magnetic resonance imaging in infants with hypoxic-ischemic encephalopathy were performed. Results: In the preterm group, pathological trace or discontinuous low-voltage pattern (p = 0.03) and absence of sleep-wake cycling (p = 0.019) were associated with mortality and brain injury assessed by cranial ultrasonography. In patients with hypoxic-ischemic encephalopathy, seizure patterns on amplitude-integrated electroencephalography traces were associated with mortality or brain lesion in cranial magnetic resonance imaging (p = 0.005). Conclusion: This study supports previous results and demonstrates the utility of amplitude-integrated electroencephalography for monitoring brain function and predicting early outcome in the studied groups of infants at high risk for brain injury.